Biometric Analysis of C-shaped Root Canals in Mandibular Second Molars Using Cone-Beam Computed Tomography - Riazifar, Negin; Amini, Kamal; Zangouyi Boushehri, Maryam; Sheikhi, Mahnaz; Karamifar, Kasra (Iranian Endodontic Journal, 2018)
Introduction: The configuration of C-shaped root canals, root canal wall thickness and orientation of the thinnest area using CBCT in mandibular second molars were assessed. Methods and Materials: Seventy five CBCT scans were evaluated. Axial sections were evaluated to determine the configuration of C-shaped canals in the coronal, middle and apical regions. The root canal path from the orifice to the apex, the thinnest root canal wall and its orientation were all determined. Data were analyzed using one-way ANOVA and post hoc Tukey’s test. Results: The most common configurations were Melton's type I in the coronal and middle and types I and IV in the apical region. The mean thicknesses of the thinnest root canal wall were 1.94±0.43, 1.42±0.57 and 1.10±0.52 mm in the coronal, middle and apical regions, respectively. The lingual wall was the thinnest wall in the coronal, middle and apical regions and it was thinner in the apical than in the middle and coronal regions. The lingual wall was thinner in the middle third of the mesial root compared to the distal root (P<0.05). Conclusion: The lingual wall was the thinnest in C-shaped root canals of mandibular second molars of an Iranian population. Type, number and pathway of canals may vary from the orifice to the apex. Keywords: Biometric Identification; C-shape Root Canal; Cone-Beam Computed Tomography